Analisis Faktor Risiko Yang Berhubungan Dengan Kejadian Karies Gigi Permanen Pada Anak Panti Asuhan Muhammadiyah Mattoanging Kecamatan Pangkajene Kabupaten Pangkep - Thioritz, Ernie; Hamid, Ellis Mirawati; Asridiana; Fachrunnisa, Andi Irmayanti (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2024)
Pangkajene and Islands Regency is one of the regions in South Sulawesi with the highest prevalence rate of dental caries, reaching 55.83%. Dental caries is the most common dental and oral health problem in Indonesia, caused by a lack of knowledge about dental hygiene, which also affects people's skills in maintaining dental and oral hygiene. One of the vulnerable social groups that needs attention is children living in orphanages. The aim of the research was to determine the relationship between knowledge level and skill level on the prevalence of permanent dental caries in children at the Mattoanging Orphanage, Pangkajene District, Pangkep Regency. This research method is classified as a quantitative research type using a cross sectional approach design. The sampling technique used was total sampling where all members of the population totaling 45 people were sampled. The statistical test scale used is Chi-square with a significance limit of 5% (α = 0.05). The results show a significant relationship between the incidence of permanent dental caries and the level of knowledge (p-value 0.019) and the level of skill in maintaining oral hygiene (p-value 0.001). The conclusion is that there is an inverse relationship between the level of knowledge and the level of skill on the incidence of dental caries. The lower a person’s knowledge and skills in maintaining oral hygiene, the higher the chance of them experiencing dental caries.